2023
DOI: 10.1007/s00438-023-02048-8
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of variants in genes associated with hypertrophic cardiomyopathy in Mexican patients

Catalina García-Vielma,
Luis Gerardo Lazalde-Córdova,
José Cruz Arzola-Hernández
et al.

Abstract: The objective of this work was to identify genetic variants in Mexican patients diagnosed with hypertrophic cardiomyopathy (HCM). According to world literature, the genes mainly involved are MHY7 and MYBPC3, although variants have been found in more than 50 genes related to heart disease and sudden death, and to our knowledge there are no studies in the Mexican population. These variants are reported and classified in the ClinVar (PubMed) database and only some of them are recognized in the Online Mendelian In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
1
0
1
Order By: Relevance
“…The authors concluded that carnitine supplementation conferred echocardiographic improvements for 6 out of 8 treated patients over periods of 3 months to 2 years. García-Vielma et al [ 28 ] sought to identify genetic variants related to hypertrophic cardiomyopathy in Mexican patients. The authors maintained that while most global research primarily pointed to genes like MHY7 and MYBPC3 , there was a dearth of data on other genes.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that carnitine supplementation conferred echocardiographic improvements for 6 out of 8 treated patients over periods of 3 months to 2 years. García-Vielma et al [ 28 ] sought to identify genetic variants related to hypertrophic cardiomyopathy in Mexican patients. The authors maintained that while most global research primarily pointed to genes like MHY7 and MYBPC3 , there was a dearth of data on other genes.…”
Section: Discussionmentioning
confidence: 99%
“…Мутации чаще всего обнаруживаются в белках -основных участниках актомиозиновой системы подвижности. До 75% случаев ГКМП, вызванных мутациями в генах саркомерных белков, приходится на MYH7 и MYBPC3, 40 и 35% соответственно [16][17][18]. Тяжёлая цепь β-миозина и миозин-связывающий белок, кодируемые генами MYH7 и MYBPC3, при участии Ca-зависимой АТФазы и за счёт гибкости миозиновой головки обеспечивают скольжение актиновых и миозиновых нитей относительно друг друга.…”
Section: значение повреждений сократительного аппарата в дисфункции м...unclassified